The unvanquished : the untold story of Lincoln's special forces, the manhunt for Mosby's Rangers, and the shadow war that forged America's special operations - O'Donnell, Patrick K., 1969- (Atlantic Monthly Press, 2024)
"From the bestselling author of The Indispensables, the unknown and dramatic story of irregular guerrilla warfare that altered the course of the Civil War and inspired the origins of America's modern special operations forces. The Civil War is most remembered for the grand battles that have come to define it: Gettysburg, Antietam, Shiloh, among others. However, as bestselling author Patrick K. O'Donnell reveals in The Unvanquished, a vital shadow war raged amid and away from the major battlefields that was in many ways equally consequential to the conflict's outcome. At the heart of this groundbreaking narrative is the epic story of Lincoln's special forces, the Jessie Scouts, told in its entirety for the first time. In a contest fought between irregular units, the Scouts hunted John Singleton Mosby's Confederate Rangers from the middle of 1863 up to war's end at Appomattox. With both sides employing pioneering tradecraft, they engaged in dozens of raids and spy missions, often perilously wearing the other's uniform, risking penalty of death if captured. Clashing violently on horseback, the unconventional units attacked critical supply lines, often capturing or killing high-value targets. North and South deployed special operations that could have changed the war's direction in 1864, and crucially during the Appomattox Campaign, Jessie Scouts led the Union army to a final victory. They later engaged in a history-altering proxy war against France in Mexico, earning seven Medals of Honor; many Scouts mysteriously disappeared during that conflict, taking their stories to their graves. An expert on special operations, O'Donnell transports readers into the action, immersing them in vivid battle scenes from previously unpublished firsthand accounts. He introduces indelible characters such as Scout Archibald Rowand; Scout leader Richard Blazer; Mosby, the master of guerrilla warfare; and enslaved spy Thomas Laws. O'Donnell also brings to light the Confederate Secret Service's covert efforts to deliver the 1864 election to Peace Democrats through ballot fraud, election interference, and attempts to destabilize a population fatigued by a seemingly forever war. Most audaciously, the Secret Service and Mosby's Rangers planned to kidnap Abraham Lincoln in order to maintain the South's independence. The first full chronicle of the shadow war between North and South, rich in action and offering original perspective on history, The Unvanquished is a dynamic and essential addition to the literature of the Civil War"--